For Recognition of a Peoples’ Right to U.N. Authorized Armed Intervention to Stop Mass Atrocities - Susan H. Bitensky (Washington University Global Studies Law Review, 2017)
This Article calls for recognition under international law of a conditional peoples’ right to United Nations (U.N.) authorized armed intervention to stop mass atrocities. The condition is that non-violent strategies must have failed or must reasonably be expected to fail in achieving this goal. If recognized, the new right will for the first time place power to obtain armed intervention in the people who are most at risk and impose a correlative duty on the U.N. to provide that intervention in qualifying cases. The right will concomitantly lift people out of the passivity of victimhood and make them active agents of their own deliverance—an amelioration consistent with and furthering human dignity. Juridically, the new right stands on remarkably strong ground. This Article relies on standard legal reasoning to discern compelling bases for the right within no less than three different categories of international law, i.e., human rights law, jus in bello, and jus ad bellum. To give the new right optimal leverage, this Article also urges certain structural reforms in the U.N. system. These include the addition of thematic mandates dedicated to stopping mass atrocities and creation of another U.N. court, this one limited exclusively to reviewing and countermanding, where appropriate, Security Council deadlocks over or rejections of armed interventions thwarting mass atrocities.
Keywords: Chapter VII; jus in bello; jus ad bellum; responsibility to protect; mass atrocities; human rights law; use of force; armed conflict; international humanitarian law